Tahlil Maudhu'at wa Manahin al-Buhuts al-'Ilmiyyah fi Syu'bah Ta'lim al-Lughah al-'Arabiyyah - Nisa', Dwi Khoirotun (Journal of Language Intelligence and Culture, 2025)
This study was conducted to solve the confusion experienced by students in selecting appropriate research topics and methodologies for writing thesis. The purpose of the study was to describe the distribution of research topics and methodologies commonly used, as well as to identify potential opportunities for further research. This research employed a library research method, with data collected through reviewing scientific research documents accessed via a digital library. The result show that: 1) the most frequently explored topics by students is: method (146 themes), speaking skills (79 themes), vocabulary (64 themes), teaching aids (61 themes), and reading skills (60 themes). 2) In terms of research method, qualitative descriptive (185 thesis) and quantitative experimental (157 thesis) were predominantly utilized. Moreover, the research and development methodology has attracted increasing attention since 2022, with 20 studies published over the past two years. 3) The study also highlighted several promising areas for future research, such as: the word of wisdom, reading, conversation, rhetoric, morphology, and composition, as well as evaluation, institutional studies, and figure studies. Likewise, there are opportunities to expand research methodologies to include correlational studies, library research, classroom action research, and research and development.